Preparation method of light C-band response MXene-Fe-coated NC-A aerogel wave-absorbing material and product thereof
By forming a single layer of MXene through etching and ultrasonic cavitation, and combining it with electrostatic assembly and freeze-drying processes, a lightweight MXene-Fe@NC-A aerogel was constructed, which solved the problems of high density and structural instability of existing microwave absorbing materials and achieved efficient C-band electromagnetic wave absorption.
Patent Information
- Application Number
- CN202510917126.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-03
- Publication Date
- 2025-11-04
AI Technical Summary
Existing absorbing materials have high density, unstable structure, and poor C-band response, making it difficult to achieve lightweight and efficient electromagnetic wave absorption.
Using Ti3AlC2 MAX ceramic as a precursor, a monolayer of MXene was formed through etching and ultrasonic cavitation. MXene-Fe-A aerogel was constructed by combining electrostatic assembly and freeze-drying. In-situ growth of Fe-ZIF nanoparticles was mediated by coordination chemistry and surface modification. Finally, a lightweight MXene-Fe@NC-A aerogel was formed by high-temperature heat treatment.
A lightweight, low-density MXene-Fe@NC-A aerogel absorbing material was prepared, exhibiting efficient C-band response characteristics and low reflection loss, making it suitable for lightweight electromagnetic compatibility applications.
Smart Images

Figure CN120897431A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electromagnetic wave absorption technology, and in particular to a method for preparing a lightweight C-band responsive MXene-Fe@NC-A aerogel absorbing material and its product. Background Technology
[0002] The application of electromagnetic wave-related technologies has greatly promoted the rapid development of electronic devices and communication technologies, bringing convenience to people's daily lives. Among them, C-band (4–8 GHz) electromagnetic waves, due to their good balance between transmission rate, penetration ability, and resistance to rain attenuation, are widely used in many key fields such as satellite communication, 5G mobile communication, and weather radar. However, with the large-scale use of C-band electromagnetic waves in daily life, the resulting electromagnetic radiation has caused significant interference to human health and the normal operation of electronic devices, which has become a major social concern. Coating relevant equipment with electromagnetic absorbing materials is an effective protection method. Currently, widely used ferrite and other absorbing materials have high density, which is detrimental to the lightweight development of equipment. Therefore, the preparation of lightweight, low-cost absorbing materials that respond in the C-band has become a research hotspot.
[0003] Two-dimensional materials, especially graphene, have been developed as microwave absorbing materials due to their large specific surface area and unique properties in terms of strength, flexibility, and tunability. Meanwhile, novel two-dimensional microwave absorbing materials are constantly being developed, particularly metal carbonitrides (MXenes), which exhibit excellent performance in tunable electronic, optical, mechanical, and electrochemical directions due to their structural diversity. Furthermore, MXenes and their derivatives possess numerous functional groups on their surface, significantly improving their dielectric loss capacity. Their conductivity can be effectively adjusted through various manipulation techniques, further enhancing their conductivity loss capacity. Additionally, as a flexible two-dimensional material, MXenes are advantageous as substrate materials for combining with other microwave absorbing materials to obtain high-performance electromagnetic wave absorbing composite materials that meet diverse needs. Therefore, developing microwave absorbing materials with ultra-light weight and high C-band response using two-dimensional MXenes is of great significance, helping to overcome the technical bottlenecks of existing MXene-based microwave absorbing materials, such as structural instability, high density, and poor effective absorption. At the same time, a low-cost and mass-producible method for preparing MXene-based microwave absorbing materials is also crucial, representing one of the technical challenges in the field of electromagnetic wave absorption. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for preparing a lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material. Using Ti3AlC2 MAX ceramic as a precursor, a monolayer MXene structure is formed through etching and ultrasonic cavitation. Then, electrostatic assembly and freeze-drying are used to construct the MXene-Fe-A aerogel. Simultaneously, through coordination chemistry and surface modification, Fe-ZIF nanoparticles and nanowires are induced to grow and tightly bind in situ within the aerogel. High-temperature heat treatment further promotes the formation of the MXene-Fe@NC-A aerogel, thereby obtaining a lightweight aerogel microwave absorbing material with high-efficiency microwave absorption capabilities. Another objective of this invention is to provide a product obtained using the above-described method for preparing the lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material.
[0005] The objective of this invention is achieved through the following technical solution:
[0006] This invention provides a method for preparing a lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material, comprising the following steps:
[0007] (1) Preparation of MXene solution with monolayer structure
[0008] (1-1) Using lithium fluoride, Ti3AlC2 MAX ceramic and hydrochloric acid solution as raw materials, the mixture was stirred and mixed according to the mass-volume ratio of lithium fluoride:Ti3AlC2 MAX ceramic:hydrochloric acid solution = 0.8-1.2g:0.8-1.2g:15-25mL. After centrifugation and washing, MXene with a multilayer structure was obtained.
[0009] (1-2) Using the multilayer MXene as raw material and deionized water as solvent, the mixture is stirred and mixed according to the mass-volume ratio of multilayer MXene:deionized water = 0.6-1.0 g:30-50 mL. Argon gas is introduced and the mixture is ultrasonically treated under ice bath conditions. The resulting suspension is centrifuged to collect the upper liquid and dispersed in deionized water to obtain a single-layer MXene solution with a concentration of 8-12 mg / mL.
[0010] (2) Preparation of MXene-Fe-A aerogel
[0011] Using the monolayer MXene solution as raw material, and combined with the metal salt FeCl2·4H2O solution, the metal salt solution : monolayer MXene solution = 1~3 : 40~60 were mixed by stirring to form an aerogel; the aerogel was freeze-dried at -80~-96℃ for 36~60h to obtain MXene-Fe-A aerogel.
[0012] (3) Preparation of MXene-Fe-ZIF-A aerogel
[0013] (3-1) Using anhydrous methanol as solvent, the MXene-Fe-A aerogel as raw material, and introducing the metal salt FeCl2·4H2O, the mixture is stirred and mixed according to the mass-volume ratio of MXene-Fe-A aerogel: metal salt: anhydrous methanol = 60-80 mg: 380-420 mg: 45-55 mL, and then allowed to stand under vacuum at room temperature to obtain solution A.
[0014] (3-2) Using anhydrous methanol as solvent, 2-methylimidazole as ligand, and combined with a surfactant, the mixture was stirred and mixed according to the mass-volume ratio of 2-methylimidazole:surfactant:anhydrous methanol = 0.7-0.8g:0.35-0.45g:45-55mL to obtain solution B;
[0015] (3-3) Using the A solution and B solution as raw materials, after stirring and mixing at room temperature, and after standing, washing and drying, MXene-Fe-ZIF-A aerogel is obtained;
[0016] (4) Preparation of MXene-Fe@NC-A aerogel
[0017] According to the mass ratio of MXene-Fe-ZIF-A aerogel to dicyandiamide = 0.8-1.2:4-6, the MXene-Fe-ZIF-A aerogel and dicyandiamide are placed at both ends of a ceramic boat and placed in a tube furnace, with the dicyandiamide placed at the inlet end and the MXene-Fe-ZIF-A aerogel placed at the outlet end; argon gas is introduced at a flow rate of 200-400 mL / min, and the temperature is increased to 700-900℃ at 5℃ / min for heat treatment for 1-4 hours, thereby obtaining a lightweight C-band response MXene-Fe@NC-A aerogel microwave absorbing material.
[0018] Further, in step (1-1) of the present invention, the concentration of the hydrochloric acid solution is 8.8–9.2 mol / L; the stirring temperature is 30–50°C, and the stirring time is 12–36 h; the centrifugation speed is 3500–4500 r / min, and the centrifugation time is 5–10 min; the washing solution is deionized water, and washing is performed until the pH value is ≥6. In step (1-2), the stirring time is 20–40 min; argon gas is introduced at a flow rate of 50–150 mL / min for 20–50 min; the ultrasonic treatment time is 45–80 min; the centrifugation speed is 1800–2200 r / min, and the centrifugation time is 15–30 min.
[0019] Furthermore, in step (2) of the present invention, the concentration of FeCl2·4H2O solution is 90-95 mg / mL; the stirring time is 5-15 min.
[0020] Further, in step (3-1) of the present invention, the stirring and mixing time is 20-50 min, the vacuum settling pressure is -0.001 to -0.02 MPa, and the settling time is 1-2 h. In step (3-2), the surfactant is polyvinylpyrrolidone, and the stirring time is 10-30 min. In step (3-3), the B solution is added dropwise to the A solution at room temperature under stirring, the stirring and mixing time is 8-15 min; the settling time is 10-16 h; the washing solution is anhydrous methanol, the washing number is 6-8 times; the drying temperature is 60-80℃, and the drying time is 24-48 h.
[0021] The product prepared using the above-described method for preparing lightweight C-band responsive MXene-Fe@NC-A aerogel absorbing material has a density of 0.4–0.8 g / cm³. 3 With a matching thickness of 1.5 to 5 mm, the C-band reflection loss at frequencies of 4 to 8 GHz is -68.69 to 0 dB.
[0022] The present invention has the following beneficial effects:
[0023] (1) This invention uses Ti3AlC2MAX ceramic as a precursor, and forms a single-layer MXene structure through etching and ultrasonic cavitation; then, it uses electrostatic assembly and freeze-drying processes to adjust Fe 2+ Electrostatic forces can be modulated by concentration and MXene surface functional group type to induce Fe 2+ A structurally stable MXene-Fe-A aerogel is formed with MXene. Then, through coordination chemistry and surface modification, Fe-ZIF nanoparticles and nanowires are induced to grow and tightly bind in situ within the aerogel. Finally, a heat treatment process promotes the carbonization of Fe-ZIF and the derivatization of dicyandiamide into carbon nanotubes, constructing a lightweight and highly efficient electromagnetic wave absorption aerogel, MXene-Fe@NC-A. This invention proposes a strategy for constructing MXene-based aerogels based on electrostatic assembly, which not only expands the types of microwave absorbing materials but also develops a material with high absorption efficiency (minimum reflection loss of -68.69 dB in the C-band (4–8 GHz) within a thickness of 1.5–5 mm) and low density (0.4–0.8 g / cm³). 3 This new type of microwave absorbing material effectively overcomes the problems of unstable structure, high density, and poor effective absorption of existing MXene-based microwave absorbing materials.
[0024] (2) This invention uses lithium fluoride and hydrochloric acid as etching agents, which can effectively etch away the Al layer in Ti3AlC2MAX, avoiding the direct use of highly corrosive hydrofluoric acid. Then, with the aid of ultrasonic cavitation, a monolayer MXene structure is formed, which is thin, has a large specific surface area, and is rich in surface functional groups. This provides Fe... 2+ This provides the possibility for electrostatic assembly and in-situ growth.
[0025] (3) This invention induces Fe through electrostatic assembly and freeze-drying process. 2+ The formation of a structurally stable MXene-Fe-A aerogel with MXene effectively inhibits the aggregation of MXene caused by interlayer van der Waals forces, while constructing a hierarchical porous structure and a high specific surface area, providing a good foundation for the subsequent growth of magnetic particles and nanotubes.
[0026] (4) This invention promotes the in-situ growth and tight bonding of Fe-ZIF in MXene aerogel through coordination chemistry and surface modification, which can promote rich heterogeneous interfaces inside the aerogel, improve the microwave absorption performance, and the constructed aerogel material has low density and exhibits lightweight characteristics, making it suitable for the field of lightweight electromagnetic compatibility.
[0027] (5) This invention provides a novel method for constructing lightweight MXene-based microwave absorbing materials with C-band response. Moreover, the process is highly repeatable, easy to control, low in cost, and easy to promote and use. Attached Figure Description
[0028] The present invention will now be described in further detail with reference to the embodiments and accompanying drawings:
[0029] Figure 1 These are scanning electron microscope images of the lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material prepared according to embodiments of the present invention;
[0030] Figure 2 This is a graph showing the relationship between reflection loss and frequency of the lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material prepared according to embodiments of the present invention at different matching thicknesses;
[0031] Figure 3 This is a graph showing the relationship between minimum reflection loss and frequency for the absorbing materials in the embodiments and comparative examples of this invention. Detailed Implementation
[0032] Example:
[0033] This embodiment describes a method for preparing a lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material, the steps of which are as follows:
[0034] (1) Preparation of MXene solution with monolayer structure
[0035] (1-1) Using lithium fluoride, Ti3AlC2 MAX ceramic, and hydrochloric acid solution (concentration of 9 mol / L) as raw materials; 20 mL of hydrochloric acid solution and 1 g of lithium fluoride were measured and transferred to a Teflon-lined container with a volume of 100 mL. 1 g of Ti3AlC2 MAX ceramic was slowly added and the mixture was magnetically stirred at 40 °C for 24 h. The resulting suspension was collected by centrifugation at 4000 r / min for 6 min and washed with deionized water until the pH value was ≥6 to obtain MXene with a multilayer structure.
[0036] (1-2) Using the above-mentioned multilayer MXene as raw material and deionized water as solvent, 0.8 g of multilayer MXene was added to 40 mL of deionized water and mixed magnetically for 30 min at room temperature. Argon gas was introduced at a flow rate of 100 mL / min for 30 min, and then ultrasonically treated under ice bath conditions for 60 min. The resulting suspension was collected by centrifugation at 2000 r / min for 20 min. The collected upper liquid was dispersed in deionized water to obtain a single-layer MXene solution with a concentration of 10 mg / mL.
[0037] (2) Preparation of MXene-Fe-A aerogel
[0038] Using the above-mentioned monolayer MXene solution as raw material, and combined with a metal salt FeCl2·4H2O solution with a concentration of 94 mg / mL; 5 mL of the monolayer MXene solution was measured and transferred to a 20 mL plastic beaker, and 0.2 mL of FeCl2·4H2O solution was added. The mixture was magnetically stirred and mixed at room temperature for 10 min. The resulting aerogel was placed in a freeze dryer and freeze-dried at -96 °C for 48 h to obtain MXene-Fe-A aerogel.
[0039] (3) Preparation of MXene-Fe-ZIF-A aerogel
[0040] (3-1) Using anhydrous methanol as solvent and the above MXene-Fe-A aerogel as raw material, and introducing the metal salt FeCl2·4H2O; 50 mL of anhydrous methanol was measured and transferred to a glass beaker with a volume of 150 mL. 400 mg of FeCl2·4H2O and 70 mg of MXene-Fe-A aerogel were added in sequence. After mixing with magnetic stirring at room temperature for 30 min, the resulting solution was placed in a vacuum drying oven and allowed to stand at room temperature for 1.5 h under a pressure of -0.01 MPa to obtain solution A;
[0041] (3-2) Using anhydrous methanol as solvent and 2-methylimidazole as ligand, and combined with the surfactant polyvinylpyrrolidone; 50 mL of anhydrous methanol was measured and transferred to a 100 mL glass beaker, and 0.8 g of 2-methylimidazole and 0.4 g of polyvinylpyrrolidone were added in sequence. After stirring magnetically for 20 min at room temperature, solution B was obtained.
[0042] (3-3) Using the above solutions A and B as raw materials, solution B was added dropwise to solution A at room temperature under stirring. The mixture was magnetically stirred for 10 min, allowed to stand for 12 h, rinsed 8 times with anhydrous methanol at room temperature, and dried at 70 °C for 36 h to obtain MXene-Fe-ZIF-A aerogel.
[0043] (4) Preparation of MXene-Fe@NC-A aerogel
[0044] 0.1g of the above-mentioned MXene-Fe-ZIF-A aerogel and 0.5g of dicyandiamide were placed at opposite ends of a ceramic boat, which was then placed in a quartz tube furnace, with the dicyandiamide at the inlet and the MXene-Fe-ZIF-A aerogel at the outlet. Argon gas was introduced at a flow rate of 300mL / min, and the temperature was increased to 800℃ at a rate of 5℃ / min for 2 hours to obtain a lightweight aerogel (density 0.43g / cm³). 3 MXene-Fe@NC-A aerogel microwave absorbing material with C-band response characteristics.
[0045] Comparative Example 1:
[0046] The MXene-Fe-A aerogel prepared in step (2) of the present invention is used as a microwave absorbing material.
[0047] Comparative Example 2:
[0048] The MXene-Fe / CA aerogel prepared without adding dicyandiamide in step (4) of the present invention is used as the microwave absorbing material.
[0049] The MXene-Fe@NC-A aerogel microwave absorbing material prepared in the embodiments of the present invention, such as Figure 1 As shown, it possesses a porous structure, abundant heterogeneous interfaces, and uniformly distributed magnetic particles and nanotubes, making it suitable for constructing next-generation lightweight and efficient MXene-based microwave absorbing materials. Figure 2 As shown, the reflection losses at matching thicknesses of 1.5mm, 2.0mm, 2.5mm, 3.0mm, 3.85mm, 4.0mm, 4.74mm, and 4.92mm within the frequency range of 2–18 GHz are -4.46dB, -9.08dB, -11.32dB, -9.37dB, -12.12dB, -13.10dB, -35.96dB, and -68.69dB, respectively.
[0050] like Figure 3 As shown, the MXene-Fe@NC-A aerogel absorbing material prepared in the embodiments of the present invention has a minimum reflection loss of -68.69 dB in the C-band at frequencies of 4–8 GHz with a matching thickness of 1.5–5 mm and a matching thickness of 4.92 mm. The electromagnetic absorbing material prepared in Comparative Example 1 is MXene-Fe-A, with a minimum reflection loss of -8.89 dB in the Ku-band at frequencies of 12–18 GHz with a matching thickness of 1.5–5 mm and a matching thickness of 1.21 mm. The electromagnetic wave absorbing material prepared in Comparative Example 2 is MXene-Fe / CA, with a minimum reflection loss of -8.68 dB in the X-band at frequencies of 8–12 GHz with a matching thickness of 1.5–5 mm and a matching thickness of 2.4 mm.
Claims
1. A method for preparing a lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material, characterized in that... Includes the following steps: (1) Preparation of MXene solution with monolayer structure (1-1) Using lithium fluoride, Ti3AlC2MAX ceramic and hydrochloric acid solution as raw materials, the mixture was stirred and mixed according to the mass-volume ratio of lithium fluoride:Ti3AlC2MAX ceramic:hydrochloric acid solution = 0.8-1.2g:0.8-1.2g:15-25mL. After centrifugation and washing, MXene with a multilayer structure was obtained. (1-2) Using the multilayer MXene as raw material and deionized water as solvent, the mixture is stirred and mixed according to the mass-volume ratio of multilayer MXene:deionized water = 0.6-1.0 g:30-50 mL. Argon gas is introduced and the mixture is ultrasonically treated under ice bath conditions. The resulting suspension is centrifuged to collect the upper liquid and dispersed in deionized water to obtain a single-layer MXene solution with a concentration of 8-12 mg / mL. (2) Preparation of MXene-Fe-A aerogel Using the monolayer MXene solution as raw material, and combined with the metal salt FeCl2·4H2O solution, the metal salt solution : monolayer MXene solution = 1~3 : 40~60 were mixed by stirring to form an aerogel; the aerogel was freeze-dried at -80~-96℃ for 36~60h to obtain MXene-Fe-A aerogel. (3) Preparation of MXene-Fe-ZIF-A aerogel (3-1) Using anhydrous methanol as solvent, the MXene-Fe-A aerogel as raw material, and introducing the metal salt FeCl2·4H2O, the mixture is stirred and mixed according to the mass-volume ratio of MXene-Fe-A aerogel: metal salt: anhydrous methanol = 60-80 mg: 380-420 mg: 45-55 mL, and then allowed to stand under vacuum at room temperature to obtain solution A. (3-2) Using anhydrous methanol as solvent, 2-methylimidazole as ligand, and combined with a surfactant, the mixture was stirred and mixed according to the mass-volume ratio of 2-methylimidazole:surfactant:anhydrous methanol = 0.7-0.8g:0.35-0.45g:45-55mL to obtain solution B; (3-3) Using the A solution and B solution as raw materials, after stirring and mixing at room temperature, and after standing, washing and drying, MXene-Fe-ZIF-A aerogel is obtained; (4) Preparation of MXene-Fe@NC-A aerogel According to the mass ratio of MXene-Fe-ZIF-A aerogel to dicyandiamide = 0.8-1.2:4-6, the MXene-Fe-ZIF-A aerogel and dicyandiamide are placed at both ends of a ceramic boat and placed in a tube furnace, with the dicyandiamide placed at the inlet end and the MXene-Fe-ZIF-A aerogel placed at the outlet end; argon gas is introduced at a flow rate of 200-400 mL / min, and the temperature is increased to 700-900℃ at 5℃ / min for heat treatment for 1-4 hours, thereby obtaining a lightweight C-band response MXene-Fe@NC-A aerogel microwave absorbing material.
2. The preparation method of the lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material according to claim 1, characterized in that: The concentration of the hydrochloric acid solution in step (1-1) is 8.8–9.2 mol / L; the stirring temperature is 30–50℃, and the stirring time is 12–36 h; the centrifugation speed is 3500–4500 r / min, the centrifugation time is 5–10 min, and the washing solution is deionized water, washing until the pH value is ≥6.
3. The preparation method of the lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material according to claim 1, characterized in that: The stirring time in steps (1-2) is 20-40 min; argon gas is introduced at a flow rate of 50-150 mL / min for 20-50 min; the ultrasonic treatment time is 45-80 min; the centrifugation speed is 1800-2200 r / min for 15-30 min.
4. The method for preparing the lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material according to claim 1, characterized in that: In step (2), the concentration of FeCl2·4H2O solution is 90-95 mg / mL; the stirring time is 5-15 min.
5. The method for preparing the lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material according to claim 1, characterized in that: The stirring and mixing time in step (3-1) is 20 to 50 minutes, the vacuum settling pressure is -0.001 to -0.02 MPa, and the settling time is 1 to 2 hours.
6. The method for preparing the lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material according to claim 1, characterized in that: In step (3-2), the surfactant is polyvinylpyrrolidone, and the stirring time is 10-30 min.
7. The method for preparing the lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material according to claim 1, characterized in that: In step (3-3), solution B is added dropwise to solution A at room temperature with stirring. The stirring time is 8-15 min; the standing time is 10-16 h; the washing solution is anhydrous methanol, and the washing is performed 6-8 times; the drying temperature is 60-80℃, and the drying time is 24-48 h.
8. A product prepared using the method for preparing a lightweight C-band responsive MXene-Fe@NC-A aerogel microwave absorbing material according to any one of claims 1-7.
9. The product according to claim 8, characterized in that: The density of the absorbing material is 0.4–0.8 g / cm³. 3 With a matching thickness of 1.5 to 5 mm, the C-band reflection loss at frequencies of 4 to 8 GHz is -68.69 to 0 dB.
